The Political Economy of Seed Reform in Uganda : Promoting a Regional Seed Trade Market - Joughin, James (World Bank, Washington, DC, 2014)
This report provides a short summary of the recent history of the seed industry. Although the informal seed system still accounts for an estimated 85 percent of planted seed, the formal sector has been transformed in 20 years from control by a monopoly parastatal to competition among 23 registered companies, with at least 5 or 6 being serious players. Significantly, the relief seed industry that dominated and distorted the formal seed trade during the Northern Uganda conflict has withered away, leaving room for a sustainable, market-driven seed industry to develop. Fundamentally, however, the key institutions in the sector and the legal framework are not fit for purpose and are a significant drag on the industry. This report sketches the roles and contribution of stakeholder organizations such as the Uganda Seed Trade Association, the Uganda National Farmers Federation, and the Uganda National Agrolnput Dealers Association. It outlines the support provided by major donors, the United States Agency for International Development (USAID), the Danish International Development Agency (Danida), the Alliance for a Green Revolution in Africa (AGRA), the Netherlands Embassy, the Food and Agriculture Organization (FAO), and the East Africa Community (EAC) Secretariat, over 15 years. After spelling out the issues in the sector, the report looks at the political economy literature for insights to help explain the near paralysis in the regulatory institutions. The dominant role of the National Resistance Movement (NRM) in decision making is described, as is the regime's use of inflationary patronage.